1998
DOI: 10.1021/bi980563b
|View full text |Cite
|
Sign up to set email alerts
|

Cu,Zn Superoxide Dismutase from Photobacterium leiognathi Is an Hyperefficient Enzyme

Abstract: The catalytic rate constant of recombinant Photobacterium leiognathi Cu,Zn superoxide dismutase has been determined as a function of pH by pulse radiolysis. At pH 7 and low ionic strength (I = 0.02 M) the catalytic rate constant is 8.5 x 10(9) M-1 s-1, more than two times the value found for all the native eukaryotic Cu,Zn superoxide dismutases investigated to date. Similarly, Brownian dynamics simulations indicate an enzyme-substrate association rate more than two times higher than that found for bovine Cu,Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…5A). It should be pointed out, however, that a significant pH dependence of activity has already been observed in the other prokaryotic Cu,Zn-SODs from P. leiognathi (43) and E. coli. 3 To influence the diffusion rate of the superoxide anion, both prokaryotic and eukaryotic Cu,Zn-SODs utilize electronic guidance by exploiting the electrostatic potential of positively charged residues on the rim of the active-site channel.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…5A). It should be pointed out, however, that a significant pH dependence of activity has already been observed in the other prokaryotic Cu,Zn-SODs from P. leiognathi (43) and E. coli. 3 To influence the diffusion rate of the superoxide anion, both prokaryotic and eukaryotic Cu,Zn-SODs utilize electronic guidance by exploiting the electrostatic potential of positively charged residues on the rim of the active-site channel.…”
Section: Resultsmentioning
confidence: 94%
“…Catalytic Activity and Electrostatics of MtSOD-In the pH 6.5-7.5 range, the enzyme displays a catalytic rate (k ϭ 2.4 ϫ 10 9 M Ϫ1 s Ϫ1 ) comparable with that of several eukaryotic enzymes (41,42), but slightly lower than that of P. leiognathi and S. typhimurium Cu,Zn-SODs (43,19). Unlike the eukaryotic enzymes, whose activity is stable up to pH 9.0, MtSOD activity drops above pH 8.0, with an inflection point at pH ϳ8.5 (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Calves that were fed milk supplemented with 25 ppm Cu and 100 ppm Zn showed a stronger immune response and a higher SOD activity [30] . Other recent reports involving SOD knockouts have revealed that Mn-SOD is essential for life whereas Cu/Zn-SOD is not.…”
Section: Superoxide Dismutasementioning
confidence: 95%
“…Cu-Zn SODs are among the fastest enzymes known, with k cat /K m values of 2.3 ϫ 10 9 M Ϫ1 s Ϫ1 for bovine SOD (33) and 8.5 Ϯ 0.8 ϫ 10 9 M Ϫ1 s Ϫ1 for the bacterial enzyme from Photobacterium legionathi (54). Functional bovine SOD is a homodimer with an intrasubunit disulfide bond within the monomer (1).…”
mentioning
confidence: 99%